Prevalence and Associations of General Practice Registrars' Management of Atopic Dermatitis: A Cross-Sectional Analysis from the Registrar Clinical Encounters in Training Study - Anneliese Willems; Amanda Tapley; Alison Fielding; Er Tsing Vivian Tng; Elizabeth Holliday; Mieke L van Driel; Jean Ball; Andrew Davey; Irena Patsan; Kristen FitzGerald; Neil Spike; Parker Magin (Mattioli1885, 2021)
Introduction: Atopic dermatitis (AD) is a chronic inflammatory condition which imposes substantial burden upon patients and their families. As a frequent primary care presentation, general practice (GP) trainees must develop adequate skills in AD diagnosis and management. Objectives: We aimed to explore the prevalence and associations of GP registrars' management of patients with AD. Methods: This study used data from the Registrar Clinical Encounters in Training (ReCEnT) project, an ongoing cohort study of the clinical and educational experience of Australian GP registrars. Registrar, patient, and consultation factors were independent variables in multivariable logistic regression with outcome factor 'diagnosis/problem being AD'. Results: From 2010-2019, 2,783 registrars (96% response rate) provided data from 381,180 consultations. AD was encountered in 0.6% of consults. AD was more likely to be seen in patients aged 0-1 years and patients from a non-English speaking background. AD was less likely to be seen in Aboriginal or Torres Strait Islander patients. Learning goals were more likely to be generated for AD and these consultations were associated with registrars seeking information or assistance. AD was strongly associated with a medication being prescribed, of which the most prescribed medications were mild or moderate potency topical corticosteroids.  Conclusions: Our findings suggest that, similar to other dermatological presentations, registrars find AD challenging to manage. There may be some gaps in AD management knowledge and application.